PENGARUH EKSTRAK DAUN PARE (Momordica charantia) TERHADAP FOLIKEL OVARIUM TIKUS (Rattus norvegicus) DALAM KONDISI HYPERGLYCEMIC - Rezady, Ganeswara Muharam Hazmi; Plumeriastuti, Hani; Rimayanti, Rimayanti (Ovozoa: Journal of Animal Reproduction, 2019)
The purpose of this study was to prove that the provision of pare leaf extract can reduce the process of follicular atrophy in the ovaries caused by hyperglycemic conditions. The total of this study was completed within 20 days, including the induction of Streptozotocin for 5 days, treatment for 14 days, and 1 day for ovarian collection. The K- group as a negative control without being induced by Streptozotocin and received no treatment. The K+ group as a positive control was only induced by Streptozotocin at a dose of 55 mg / Kg BW and D10 without treatment. The T1 group was induced by Streptozotocin at doses of 55 mg / Kg BW and D10 and treated with pare leaves extract (Momordica charantia) at a dose of 1.26 ml / Kg BW. T2 group was induced by Streptozotocin with dose of 55 mg / Kg BW and D10 and was treated with pare leaves extract (Momordica charantia) at a dose of 2.52 ml / Kg BW. Induction of Streptozotocin intraperitoneally and once-daily peroral treatment. The result showed that treatment group could make a significant difference with the positive control. Showing that amount of gap could make Momordica charantia to be alternative treatment for hyperglycemic condition.